Grain Inoculated with Different Growth Stages of the Fungus, Aspergillus flavus, Affect the Close-Range Foraging Behavior by a Primary Stored Product Pest, Sitophilus oryzae (Coleoptera: Curculionidae). Issue 5 (14th August 2022) - Ponce, Marco A; Lizarraga, Sandra; Bruce, Alexander; Kim, Tania N; Morrison, William R
Abstract: Although some research has investigated the interactions among stored product insects and microbes, little research has examined how specific fungal life stages affect volatile emissions in grain and linked it to the behavior of Sitophilus oryzae, the cosmopolitan rice weevil. Thus, our goals were to 1) isolate, culture, and identify two fungal life stages of Aspergillus flavus, 2) characterize the volatile emissions from grain inoculated by each fungal morphotype, and 3) understand how microbially-produced volatile organic compounds (MVOCs) from each fungal morphotype affect foraging, attraction, and preference by S. oryzae . We hypothesized that the headspace blends would be unique among our treatments and that this will lead to preferential mobility by S. oryzae among treatments. Using headspace collection coupled with GC-MS, we found the sexual life stage of A. flavus had the most unique emissions of MVOCs compared to the other semiochemical treatments. This translated to a higher interaction with kernels containing grain with the A. flavus sexual life stage, as well as a higher cumulative time spent in those zones by S. oryzae in a video-tracking assay in comparison to the asexual life stage. While fungal cues were important for foraging at close-range, the release-recapture assay indicated that grain volatiles were more important for attraction at longer distances. There was no significant preference between grain and MVOCs in a four-way olfactometer. Overall, this study enhances our understanding of how fungal cues affect the close and longer range foraging ecology of a primarily stored product insect. Graphical Abstract: